Increasing the Nutritional Value of Camelina Meal via Trametes versicolor Solid-State Fermentation with Various Co-Substrates - Kristin Boardman; Xiao Sun; Dana Yao; Chi Chen; Leif van Lierop; Bo Hu (Fermentation)
Upcycling low-cost agricultural by-products into valuable and sustainable alternative feeding materials could secure human food-supply chains with a low carbon footprint. This study explored increasing the feeding value of camelina meal (CAM) mixed with wheat bran (WB), soybean hulls (SH), and rice hulls (RH) for monogastric animals via solid-state fermentation (SSF) using white rot fungus Trametes versicolor. Experiments evaluated fungal growth, amino acid profiles, structural carbohydrates, glucosinolates, phytate and in vitro dry matter digestibility (IVDMD). Weight loss analysis indicated that fungal growth was more active in WB/CAM and SH/CAM substrates than RH/CAM. Significant phytic acid degradation and near-complete glucosinolate elimination improved CAM feed quality across all substrates. Fermentation increased total and essential amino acids in the SH/CAM mixture, while reductions occurred in WB/CAM and RH/CAM mixtures. SH/CAM fermentation caused substantial cellulose and hemicellulose degradation, resulting in a 44% IVDMD increase. Conversely, RH/CAM fermentation decreased IVDMD despite a reduction in cellulose, possibly due to protein degradation. This study demonstrates the potential of T. versicolor-mediated SSF to enhance CAM and other agricultural residues’ feeding value for monogastric animal applications.